Characteristic of acute illness of higher education students - Reznichenko, Oleksandr; Gridnieva, Svitlana; Martynenko, Maksym (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2020)
Abstract. The problem of student health has become of great importance in recent decades and remains unresolved at the current time. The article presents the data of the study of acute morbidity of students of higher educational establishments, its frequency and structure, the gender peculiarities and the state of resistance of their organism are analyzed. Highlighted the priority diseases groups, their specificity and differences. According to the results of the study, the state of adaptation of the students’ body in the first year of study was revealed. At the same time, there are signs of tension and breakdown of these mechanisms, decrease in body resistance may be primarily due to sudden changes in the habitual environment of students, impaired diet and quality of work-rest cycle, the presence of a large number of students who have bad habits, constant increase of educational and information load in the present conditions. Only 18.46 ± 1.16 % of medical high schools and even fewer students of technical high schools have 7.81 ± 0.63 % satisfactory indicators of resistance to the body, which indicates a possible discrepancy between the impact of the educational complex and external factors to the adaptive capacity of the student body. In the structure of acute morbidity prevail respiratory diseases in both study groups (KhNMU − 80.16 ± 2.58 %, KhNURE − 80.37 ± 2.61 %). Also, quite a large part was taken by diseases of the digestive system and urogenital system. Students of a technical university had worse indicators of body resistance compared to students of a medical university. It was also found that boys had poorer body resistance compared to girls in all groups. In future all this has negative social and economic consequences for the country as a whole.